The treatment effect of silymarin on heart damage in rats (Annals of Medical Research, 2021)
Aim: In this article, we evaluated the possible cardiac protective effects of silymarin on valproic acid-induced heart injury by histological and biochemical parameters in rat heart.Material and Methods: The experiment was performed with 21 Sprague Dawley male rats. Rats were divided into three groups: group 1; control, group 2; valproic acid, group 3; valproic acid + silymarin. The groups received valproic acid 500 mg/kg/day per os (p.o.) and silymarin 100 mg/kg/day p.o. for 14 days except the control group.Results: Silymarin treatment decreased the levels of lactate dehydrogenase, creatine kinase isoenzyme MB, alanine aminotransferase and aspartate aminotransferase significantly (p 0.05). In addition, the increase of malondialdehyde level and decrease of glutathione level by valproic acid were significantly suppressed by silymarin in heart tissue (p 0.05). Histologically, the amount of heart injury was significantly lower in valproic acid + silymarin group and histopathological findings were decreased in valproic acid + silymarin group compared to valproic acid group (p 0.005).Conclusion: In this study, it was observed that silymarin has a curative effect on valproic acid induced heart damage. In this sense, we believe that our study will be usefull for other studies which will be study with silymarin and valproic acid.
Keywords: Heart damage; rat; silymarin; valproic acid